Chapter Wage Concentration in Spain: A Spatial Analysis - Pavía, Jose M. (InTechOpen, 2016)
This chapter overviews different approaches for the synthesis of nanostructured materials based on alternative methodologies to the most conventional and widespread colloidal wet chemical route and with a great potential applicability to large-scale and continuous production of nanomaterials. Their major outcomes, current progress in synthesis of micro and nanostructures by using microfluidics techniques and potential applications for the next future are reviewed throughout three different sections. Emphasis is placed on nanomaterials production basics, nanomaterials production techniques and microfluidic reactors (types, materials, designs). The integration of nanoparticle and microreactor technologies delivers enormous possibilities for the further development of novel materials and reactors. In this chapter, recent achievements in the synthesis of nanoparticles in microfluidic reactors are stated. A variety of strategies for synthesizing inorganic and polymeric nanoparticles are presented and compared, including continuous flow, gas-liquid segmented flow and droplet-based microreactors